Mapping technologies to business models: An application to clean technologies and entrepreneurship - Julian Oliver Dörr (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Theory suggests that new market entrants play a special role for the creation of new technological pathways required for the development and diffusion of more sustainable forms of production, consumption, mobility and housing. Unconstrained by past technological investments, entrants can introduce more radical environmental innovations than incumbent firms whose past R&D decisions make them locked into path-dependent trajectories of outdated technologies. Yet, little research exists which provides empirical evidence on new ventures' role in the technological transition towards decarbonization and dematerialization. This is mainly because patenting is rare among start-ups and also no historical track record about their R&D investments exists, both data sources commonly used to determine a company's technological footprint. To enable the identification of clean technology-oriented market entrants and to better understand their role as adopters and innovators for sustainable market solutions, this paper presents framework that systematically maps new ventures' business models to a set of well-defined clean technologies. For this purpose, the framework leverages textual descriptions of new entrants' business summaries that are typically available upon business registration and allow for a good indication of their technological orientation. Furthermore, the framework uses textual information from patenting activities of established innovators to model semantic representations of technologies. Mapping company and technology descriptions into a common vector space enables the derivation of a fine-granular measureof entrants' technological orientation. Applying the framework to a survey of German start-up firms suggests that clean technology-oriented market entrants act as accelerators of technical change: both by virtue of their existing products and services and through a high propensity to introduce additional environmental innovations.
Keywords: C38; O13; Q55; 330; Clean technologies; technological orientation; environmental innovation; sustainable entrepreneurship; text modeling; natural language processing